2008
DOI: 10.1177/1933719108314624
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF but Not Amphiregulin or Their Receptors HER1 and HER4 Is Altered in Endometrium of Women With Unexplained Infertility

Abstract: Heparin-binding epidermal growth factor-like growth factor (HB-EGF) and its receptors (HER1 and HER4) play a role in the human implantation process. Amphiregulin is a member of the EGF family but with unknown function in human fertility. It has been suggested that some women with unexplained infertility have defective endometrial development. The aim of this study is to determine the presence of amphiregulin and the receptors HER1 and HER4 in normal human endometrium throughout the menstrual cycle. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
(77 reference statements)
2
16
0
Order By: Relevance
“…Epidermal growth factor receptor (ERBB1) expression in normal eutopic endometrium on the mRNA and protein levels during different menstrual cycle phases was demonstrated herein and confirms earlier reports. 31-33 We have observed that EGFR gene expression is increased in eutopic endometrium of women with severe endometriosis compared to women without disease in ESE and MSE, but not PE, and is not regulated in mild endometriosis versus nonendometriosis samples throughout the cycle (Aghajanova et al, unpublished data). Herein, we have found that EGFR is dysregulated in severe versus mild endometriosis throughout the menstrual cycle on both mRNA and protein levels, with the most dramatic difference (upregulation) in ESE.…”
Section: Discussionmentioning
confidence: 96%
“…Epidermal growth factor receptor (ERBB1) expression in normal eutopic endometrium on the mRNA and protein levels during different menstrual cycle phases was demonstrated herein and confirms earlier reports. 31-33 We have observed that EGFR gene expression is increased in eutopic endometrium of women with severe endometriosis compared to women without disease in ESE and MSE, but not PE, and is not regulated in mild endometriosis versus nonendometriosis samples throughout the cycle (Aghajanova et al, unpublished data). Herein, we have found that EGFR is dysregulated in severe versus mild endometriosis throughout the menstrual cycle on both mRNA and protein levels, with the most dramatic difference (upregulation) in ESE.…”
Section: Discussionmentioning
confidence: 96%
“…It remains to be established whether the reduced expression of HBEGF precedes the onset of preeclampsia or if it is merely associated with late placental demise. There is also clinical evidence of HBEGF disruption associated with infertility in women (Aghajanova et al, 2008). The decreased HBEGF expression in infertile couples was not confirmed in a larger clinical study, but it was noted that a significant increase between the early and mid secretory phases was absent in the infertile patients (Leach et al, 2012).…”
Section: Human Placentationmentioning
confidence: 99%
“…HB-EGF activation of ErbB1/4 receptors involves bidirectional interactions between the blastocyst and the uterus prior to implantation in mice (Das et al, 1994; Hamatani et al, 2004b; Paria et al, 1999a; Paria et al, 2001a; Raab et al, 1996; Wang et al, 2000; Xie et al, 2007), and a similar machinery functions during human implantation and placentation (Birdsall et al, 1996; Chobotova et al, 2005; Chobotova et al, 2002a; Chobotova et al, 2002b; Gonzalez et al, 2011; Jessmon et al, 2009; Leach et al, 1999; Lessey et al, 2002; Yoo et al, 1997). Moreover, aberrant expression of HB-EGF in human trophoblasts is associated with preeclampsia (Aghajanova et al, 2008a; Leach et al, 2002). In addition, homeobox transcription factors and developmental morphogenesis genes essential for uterine function and implantation in mice exhibit dynamic expression patterns in human endometrium and potential association with certain pregnancy complications (Bombail et al, 2010; Cheng et al, 2008; Kodama et al, 2010; Koler et al, 2009; Li et al, 2007; Mirkin et al, 2005; Taylor, 2000; Taylor et al, 1998; Taylor et al, 1997; Tulac et al, 2006).…”
Section: Implications For Human Fertilitymentioning
confidence: 99%